An Acute Bout of Soccer Heading Subtly Alters Neurovascular Coupling Metrics - Smirl, Jonathan D.; Peacock, Dakota; Wright, Alexander D.; Bouliane, Kevin J.; Dierijck, Jill; Burma, Joel S.; Kennefick, Michael; Wallace, Colin; van Donkelaar, Paul (Frontiers in Neurology, 2020)
Objective: The current investigation examined how a bout of soccer heading may impact brain function. Design: Semi-randomized crossover cohort. Setting: Controlled soccer heading. Participants: Seven male soccer players (24.1 ± 1.5 years). Intervention: 40 successful soccer headers were performed in 20 min (25 m, launch velocity ~80 km/h). X2 xPatch recorded linear and rotational head accelerations during each impact. A contact control “sham” condition – ball made body contact, but not by the head; and a no activity time “control” condition were also completed. Main Outcome Measures: Posterior and middle cerebral artery (PCA and MCA, respectively), cerebral blood velocity (CBV) was recorded during a visual task (neurovascular coupling: NVC) alongside SCAT3 symptoms scores pre/post a controlled bout of soccer heading. Results: Cumulative linear and rotational accelerations were 1,574 ± 97.9 g and 313,761 ± 23,966 rads/s2, respectively, during heading and changes in SCAT3 symptom number (pre: 2.6 ± 3.0; post: 6.7 ± 6.2, p = 0.13) and severity (pre: 3.7 ± 3.6, post: 9.4 ± 7.6, p = 0.11) were unchanged. In the PCA, no NVC differences were observed, including: relative CBV increase (28.0 ± 7.6%, p = 0.71) and total activation (188.7 ± 68.1 cm, p = 0.93). However, MCA-derived NVC metrics were blunted following heading, demonstrating decreased relative CBV increase (7.8 ± 3.1%, p = 0.03) and decreased total activation (26.7 ± 45.3 cm, p = 0.04). Conclusion: Although an acute bout of soccer heading did not result in an increase of concussion-like symptoms, there were alterations in NVC responses within the MCA during a visual task. This suggests an acute bout of repetitive soccer heading can alter CBV regulation within the region of the brain associated with the header impacts.